Individual cognitive therapy reduces frontal-thalamic resting-state functional connectivity in social anxiety disorder - Kurita, Kohei; Obata, Takayuki; Sutoh, Chihiro; Matsuzawa, Daisuke; Yoshinaga, Naoki; Kershaw, Jeff; Chhatkuli, Ritu Bhusal; Ota, Junko; Shimizu, Eiji; Hirano, Yoshiyuki (Frontiers in Psychiatry, 2023)
Introduction: Previous neuroimaging studies in social anxiety disorders (SAD) have reported potential neural predictors of cognitive behavioral therapy (CBT)-related brain changes.However, several meta-analyses have demonstrated that cognitive therapy (CT) was superior to traditional exposure-based CBT for SAD. Objective: To explore resting-state functional connectivity (rsFC) to evaluate the response to individual CT for SAD patients. Methods:Twenty SAD patients who attended 16-week individual CT were scanned pre-and post-therapy along with twenty healthy controls (HCs). The severity of social anxiety was assessed with the Liebowitz Social Anxiety Scale (LSAS). Multi-voxel pattern analysis (MVPA) was performed on the pre-CT data to extract regions associated with a change in LSAS (∆LSAS). Group comparisons of the seed-based rsFC analysis were performed between the HCs and pre-CT patients and between the pre-and post-CT patients. Results: MVPA-based regression analysis revealed that rsFC between the left thalamus and the frontal pole/inferior frontal gyrus was significantly correlated with ∆LSAS (adjusted r 2 = 0.65; p = 0.00002). Compared with HCs, the pre-CT patients had higher rsFCs between the thalamus and temporal pole and between the thalamus and superior/middle temporal gyrus/planum temporale (p < 0.05). The rsFC between the thalamus and the frontal pole decreased post-CT (p < 0.05). Conclusion: SAD patients had significant rsFC between the thalamus and temporal pole, superior/middle temporal gyrus, and planum temporale, which may be indicators of extreme anxiety in social situations. In addition, rsFC between the thalamus and the frontal pole may be a neuromarker for the effectiveness of individual CT.